MEKANISME BERACARA SECARA PRODEO DALAM PERKARA PERDATA - Purwata, I Ketut Gede Pasek; Eka Wisanjaya, I Gede Pasek (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
Litigants to litigate in a court fee waiver for free - free foreign court, for people who cannot afford to not be able to attach a letter from the head of the village, covering an area of law where the requester litigants live in without cost, and explain that the person is completely unable to pay for court case petition the case will be rejected by the court without cost if the plaintiff was not a person who can’t afford. But for those who are less able, can file a lawsuit for free - free is called the litigants are without cost.
Keywords: Procedural, Mechanism, Cost in Civil Case